Mentoring in the Rostov-on-Don anti-plague institute and information link between generations - I. A. Shchipeleva; E. I. Markovskaya; О. F. Kretenchuk; O. S. Chemisova (Медицинский вестник Юга России, 2021)
The article presents the experience of using mentoring as the most effective method of adapting new employees to fully include them in the work of the Rostov-on-don anti-plague Institute. The purpose of the study was to analyze the work on mentoring in the Rostov-on-Don anti-plague Institute and to compare the experience of the Institute with the work in this direction in other institutions in Russia and abroad. It was shown how important the mentoring process was when working with pathogens of groups I–II of pathogenicity, including during the fight against the novel coronavirus infection COVID-19. The importance of mentoring when immersed in the scientific environment, when motivating to acquire new knowledge, and striving for innovative results in their research was also noted. Mentoring is a modern method of personnel work that provides quick adaptation, professional development, and career growth, and has a positive effect on the stability of the institution as a whole.